ANALISIS TEMA UNGKAPAN TRADISIONAL BAPENO DI DESA HIANG KECAMATAN SITINJAU LAUT KABUPATEN KERINCI PROVINSI JAMBI - Erwin Gunawan; Ade Rahima; Supriyati Supriyati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research is intended to describe the theme of bapeno traditional expression . the data of this research is words in the traditional expression of bapeno. The data is collected by using observation, interview, recording, and documentation. This research is qualitative descriptive that are analyzed by using sturctural approach and content analysis. This result of the research shows that there are 2 themes found, they are: theme about the relationship of human with human and the relationship of human and God. Those results are acquired from 32 sentences which represent the relationship of human with human and 13 sentences which represent the relationship of human and God.Key Words : theme, traditional expression, bapeno